Dielectric, AC conductivity and optical properties of mixed ionic-electronic 20Li₂O-ₓBi₂O₃-(80-ₓ)TeO₂ tellurite glass / Siti Wahidah Nazari - Nazari, Siti Wahidah (2017)
Mixed ionic electronic 20Li2O-xBi2O3-(80-x)TeO2; (x = 3-15 mol%) glasses have been prepared by melt-quenching method to investigate the effect of bismuth on dielectric and ac conductivity behaviors. Structural properties of the glasses was investigated by Fourier Transform Infrared (FTIR) spectroscopy. Dielectric properties, ac conductivity and modulus formalism of the glasses were investigated by using impedance spectroscopy measurements in the frequency range of 0.01 Hz to 1MHz and in the temperature range of 323 K - 473 K. IR spectra of the present glass system shows Bi2C>3 plays the role of network former with B1O3 unit structure at JC < 7 mol% but acts as network modifier with Bi06 unit structure for x > 10 mol%. Transference number measurements showed the glasses were initially predominantly ionic for x < 7 mol% before a large drop in ionic contribution accompanied by increase in electronic carrier for x > 10 mol% where the glasses transform into mixed ionic electronic glass with ionic conduction still as the major component. The dielectric constant s' and ac conductivity showed increasing trend with the increase in Bi203 except for an unexpected drop at x = 7 mol%. The anomalous drop is suggested to be due to mixed ionic electronic (MIE) effect which involves some form of hindering effect of Bi203 on Li+ ions. The drop in ionic conductivity in the x > 10 mol% region is suggested to be due to some form of hindering effect of the heavier Bi3+ on Li+ . AC conductivity showed weaker dispersion at low frequency (f< 100Hz) and exhibited stronger dispersion at higher frequency (f > 100Hz) where in the dispersion region, the charge transport mechanism was found to be Correlated Barrier Hopping (CBH) for all glass samples except for x - 7 mol% where the charge transport mechanism was Overlapping Large Polaron Tunneling (OLPT) at low frequency (f < 100Hz) and CBH mechanism at high frequency (f > 100Hz) respectively. The imaginary part of electrical modulus spectra was fitted to the Kohlrausch-Williams-Watts (KWW) stretched exponential function and the value of the stretched exponent, /? which represents the degree of interaction between the ions was found to be dependent on composition. Bi2C>3 addition to 20Li2O-xBi2O3-(80- x)Te02 glasses resulted in slow decrease of optical band gap .Eoptup to x = 13 mol% before a large drop at higher Bi2C>3 content (x = 15 mol%). This optical behaviour is suggested to be related to changes in non bridging oxygen NBO content in the glass system in conjunction to presence of defects in the glasses. Urbach energy Eu shows opposite behaviour with iiopt indicating electron transition from the top of valence band to lowest defect state. On the other hand, the variation of refractive index n is influenced by electronic polarizability a 2 ~. Addition of bismuth at x > 7 mol% showed n increased due to increase in